Copper (II) Phthalocyanine (CuPc) Based Optoelectronic Memory Device with Multilevel Resistive Switching for Neuromorphic Application. (12th March 2021) - Das, Biswajit; Samanta, Madhupriya; Sarkar, Pranab; Ghorai, Uttam K.; Mallik, Abhijit; Chattopadhyay, Kalyan K.
Abstract: The 1D nanotubular organic semiconductor, copper (II) phthalocyanine (CuPc), embedded in poly‐methyl methacrylate (PMMA) is employed for the first time for multilevel resistive switching (RS) and neuromorphic applications. Single–double bonded planar CuPc tubes are synthesized via simple solvothermal methods and dispersed in the PMMA solution with different weight concentrations. The composite sample is deposited on an ITO coated transparent, flexible and conducting PET substrate to form Ag/CuPc@PMMA/ ITO device. I – V characterizations of the cell reveal a formation free, bipolar, non‐volatile, multilevel RS effect. The device shows a significantly large resistance ON/OFF ratio of 10 4, low threshold operating voltage (<2 V), large endurance (>10 4 cycles) and long retention time (>10 4 s) at room temperature. The multilevel resistive states are induced by visible light illumination. Based on the experimental data, the conduction mechanism of this type of RS memory device under the optical and the electrical impulse is attributed by the charge trapping and detrapping methods. The synaptic short‐term and long‐term potentiation are also studied on the device during the identical pulse training process. The proposed RS active material is a potential candidate for future artificial neural systems that simulate characteristics of human memory. Abstract : A copper phthalocyanine nanotube based flexible device showing both memory switching and neuromorphic application is fabricated on conducting polyethylene terephthalate (PET) substrate via a simple and scalable approach. Resistive switching behaviour in the presence of visible light is also investigated. Our proposed device can act as a potential candidate for future artificial neural systems that simulate the characteristics of human memory.